From the UK Abortion Act 1967 to the present: the woman’s decision-making journey (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The aim of this paper is to analyse the relationship between women’s empowerment on the issue of abortion and their need for a supportive and informed deliberative process in the UK scenario. The UK Abortion Act 1967 and current proposals to change the law on abortion, though starting from different places, seem not to properly tackle the complexity behind the woman’s decision-making process. The paper focuses on the two most relevant factors, timing and reasons, involved in the woman’s deliberative process concerning termination of pregnancy, pointing out the strengths and weaknesses in the law and medical guidelines when it comes to safeguarding this process. From the 1960s to the present the British Medical Association (BMA) and the Royal College of Obstetricians and Gynaecologists (RCOG) – two of the main stakeholders – have shown a clear shift in their approach to the law on abortion and related policies from a more medical approach to a wider focus on women’s personal choice. Nonetheless this shift – which has been reflected in new legislative proposals to amend the Abortion Act 1967 – should not compromise recognition of women’s need to receive the social and medical support they deserve during a challenging and possibly life changing process.
Keywords: Abortion; clinical guidelines; decriminalization; deliberative process; woman’s autonomy